Manufacturing method of multilayer inductor

By using silver powder with different particle sizes in silver powder and increasing the copper content in the second silver powder, the problem of difficult to take into account in the prior art is solved, and a conductive film with high filling rate, high density and low migration is achieved, while maintaining high conductivity and good printing performance.

JP7663140B2Active Publication Date: 2025-04-16SHOEI CHEM IND CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024023679
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-26
Filing Date
2024-02-20
Publication Date
2025-04-16
Estimated Expiration
2039-11-28

AI Technical Summary

Technical Problem

The prior art is difficult to maintain good printing performance while maintaining high conductivity and density coatings, especially in preventing silver powder migration.

Method used

Two silver powders of different particle sizes are used, the first silver powder (D50 3.50 to 7.50 microns) and the second silver powder (D50 0.80 to 2.70 microns), where the second silver powder contains 80% or more copper, and the first silver powder contains almost no copper to achieve a high density and low migration conductive film.

Benefits of technology

A balance between high silver powder concentration and good printing performance is achieved, and a conductive film with high filling rate, high density and low migration is obtained, while maintaining high conductivity and good printing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663140000004
    Figure 0007663140000004
  • Figure 0007663140000005
    Figure 0007663140000005
  • Figure 0007663140000006
    Figure 0007663140000006
Patent Text Reader

Abstract

To provide a method of manufacturing a silver paste containing a powder at a high concentration, and having an excellent printability, and provide a silver conductive film that uses the silver paste, of which a filling factor and a film density are high, which indicates a high conductivity, and an excellent migration resistance.SOLUTION: A silver paste contains at least silver powder, a binder resin, and an organic solvent, in which the silver powder satisfies all of the following conditions [1] to [4]: [1] A first silver powder of which D50 is 3.50 to 7.50 μm when a value of 50% in an integration fraction of a volume reference of a laser diffraction type grain distribution measurement is the D50, and a second silver powder of which the D50 is 0.80 to 2.00 μm are contained; [2] a copper content amount of a whole silver powder is 10 to 5000 mass ppm; [3] the copper content amount of the second silver powder is 80 mass ppm or more; and [4] the first silver powder does not actually contain a copper.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sintered silver paste that contains silver powder and is used to form internal and external electrodes in ceramic electronic components such as multilayer ceramic capacitors, inductors, and actuators. [Background technology]

[0002] Conventionally, conductive pastes containing metal powders have been widely used to form internal and external electrodes of electronic components. One of the reasons for this is that, compared with conductive inks using organometallic compounds, conductive pastes containing metal powders can be used with various printing methods such as screen printing, offset printing, gravure printing, inkjet printing, dipping, dispensing, brushing, and spin coating, and can form thick films by a single coating and printing process, making them advantageous in terms of obtaining high conductivity.

[0003] In order to obtain high conductivity, it is preferable that the conductive paste contains a high content of metal powder, and it is also desirable that the coating film obtained by printing the paste is dense and high density. By using a high content of metal powder, reliable conduction can be obtained even in the formation of finer patterns in the future.

[0004] For example, Patent Document 1 (JP Patent Publication No. 2005-174824) discloses an invention that uses metal colloid particles instead of metal powder to obtain a highly dense and conductive film, and uses an organometallic compound in combination with this to fill the gaps between the metal colloid particles with the organometallic compound, thereby increasing the density.

[0005] However, since metal colloid particles and organometallic compounds contain a large amount of organic components, when these are used as the main conductive component, the content of the metal components is lower than that of pastes using metal powders, and therefore a conductor film with low resistivity cannot be obtained. Moreover, it is difficult to deal with the above-mentioned wide variety of printing methods, and if a large amount of binder resin or viscosity modifier is added to the paste to solve this problem, the metal ratio in the coating film will be further reduced.

[0006] On the other hand, when metal powder is used as the conductive component of the paste, a conductive film with low resistivity can be obtained if the content of the metal powder is high, but the higher the content of the metal powder, the worse the printability becomes. Therefore, in the case of silver paste, for example, the highest coating density described in Patent Document 2 is 5.4 g / cm. 3 The maximum coating density described in Patent Document 3 is 5.70 g / cm 3 In addition, Patent Document 4 describes a nickel paste with a dry film density of 6.2 g / cm. 3 Examples are disclosed.

[0007] As described above, when trying to obtain a dense coating film with high conductivity in a conductive paste, printability is sacrificed, and there is a trade-off between the two. Therefore, there is a demand for a conductive paste that can simultaneously achieve dense coating film formation and good printability.

[0008] There are known examples of using two types of silver powder with different particle sizes, large and small, to obtain a dense coating film (Patent Document 5 and Patent Document 6). However, a phenomenon called migration is known to occur, particularly in the case of silver paste that uses silver powder, and the more small-diameter silver powder (e.g., less than 0.5 μm) contained in the silver paste, the more likely migration is to occur.

[0009] Conventionally, various measures have been attempted to suppress migration, such as adding a migration inhibitor containing fluorine to silver paste (Patent Document 7) or adding a mixed powder, alloy powder, or compound powder containing the three elements of copper, tin, and manganese to silver powder (Patent Document 8). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2005-174824 A [Patent Document 2] JP 2007-131950 A [Patent Document 3] JP 2008-192565 A [Patent Document 4] JP 2004-220807 A [Patent Document 5] JP 2003-280179 A [Patent Document 6] JP 2005-203304 A [Patent Document 7] JP 2014-197483 A [Patent Document 8] International Publication No. 2014 / 061765 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0011] However, adding a large amount of components other than the silver powder as described above to the paste for the purpose of preventing migration is not preferable in terms of obtaining high electrical conductivity.

[0012] Therefore, the present invention aims to solve these problems. That is, the object of the present invention is to provide a silver paste containing a high concentration of silver powder and having excellent printability, and thereby to provide a silver conductor film having a high filling rate and film density, high conductivity, and excellent migration resistance. [Means for solving the problem]

[0013] As a result of intensive studies to solve the above problems, the present inventors have found that even when the paste contains a high concentration of silver powder, [1] when the 50% value in the volume-based cumulative fraction of laser diffraction particle size distribution measurement is taken as D50, a first silver powder (a) having a D50 of 3.50 to 7.50 μm and a second silver powder (b) having a D50 of 0.80 to 2.70 μm are used in combination as the silver powder, [2] the copper content of the entire silver powder is 10 to 5000 mass ppm, [3] the copper content of the second silver powder (b) is 80 mass ppm or more, and [4] the first silver powder (a) is substantially free of copper. By doing so, a dense dried film can be obtained without sacrificing printability, and migration can be effectively suppressed by simply containing the minimum necessary copper component in the silver powder, and the present invention has been completed.

[0014] That is, the present invention (1) is a silver paste containing at least silver powder, a binder resin, and an organic solvent, The silver powder is selected from the following [1] to [4]: [1] The present invention includes a first silver powder (a) having a D50 of 3.50 to 7.50 μm and a second silver powder (b) having a D50 of 0.80 to 2.70 μm, where D50 is the 50% value in the volume-based cumulative fraction determined by laser diffraction particle size distribution measurement; [2] The copper content of the entire silver powder is 10 to 5000 ppm by mass; [3] The copper content of the second silver powder (b) is 80 ppm by mass or more; [4] the first silver powder (a) is substantially free of copper; The above conditions must all be met. The present invention provides a silver paste characterized by the above.

[0015] In addition, the present invention (2) is characterized in that, when the 10% value in the volume-based cumulative fraction of a laser diffraction particle size distribution measurement is defined as D10, the second silver powder ( bThe present invention provides a silver paste according to claim 1, characterized in that the D10 of the silver paste is 0.70 μm or more.

[0016] The present invention (3) also provides the silver paste of either (1) or (2), characterized in that the copper content of the first silver powder (a) is less than 50 ppm by mass.

[0017] The present invention (4) also provides a silver paste according to any one of (1) to (3), wherein the first silver powder (a) has a D50 of 3.70 to 7.50 μm.

[0018] The present invention (5) also provides the silver paste of any one of (1) to (3), wherein the first silver powder (a) has a D50 of 4.00 to 6.00 μm.

[0019] The present invention (6) also provides the silver paste of any one of (1) to (5), wherein the second silver powder (b) has a D50 of 0.80 to 2.00 μm.

[0020] The present invention (7) also provides a silver paste according to any one of (1) to (6), wherein the silver powder as a whole has a D10 of 1.00 to 3.00 μm and a D50 of 3.00 to 7.00 μm.

[0021] The present invention (8) also provides a silver paste according to (7), wherein the silver powder as a whole has a D10 of 1.20 to 2.00 μm.

[0022] The present invention (9) also provides the silver paste of either (7) or (8), characterized in that the silver powder as a whole has a D50 of 3.90 to 5.00 μm.

[0023] The present invention (10) also provides a silver paste according to any one of (1) to (9), wherein the total copper content of the silver powder is 30 to 500 ppm by mass.

[0024] The present invention (11) further comprises the following [5]: [5] The total content of the silver powder in the silver paste C AG is 80.00 to 97.00 mass%; The present invention provides a silver paste according to any one of (1) to (10) above, which satisfies the above conditions.

[0025] In addition, the present invention (12) relates to the total content C of the silver powder in the silver paste. AG The silver paste according to claim 11, wherein the content of the silver in the silver paste is 92.00 to 96.00 mass %.

[0026] In addition, the present invention (13) is characterized in that the dry film density of the silver paste is 7.50 g / cm 3 The present invention provides a silver paste according to any one of (1) to (12) above, characterized by the above.

[0027] In addition, the present invention (14) provides a method for obtaining a specific surface area of ​​the entire silver powder by S BET (m 2 / g), and the content ratio of the binder resin to the total silver powder is C BND (mass%), C BND / S BET The present invention provides a silver paste according to any one of (1) to (13), characterized in that the value of (i) is 2.00 to 3.40.

[0028] In addition, the present invention (15) provides a method for producing a silver powder having a specific surface area S BET 0.10~0.30m 2 / g.

[0029] The present invention (16) also provides a silver paste according to any one of (1) to (15), which is used for forming a conductor film by a heat treatment at 700° C. or less. Effect of the Invention

[0030] According to the present invention, it is possible to provide a silver paste containing a high concentration of silver powder and having excellent printability, and thereby to provide a silver conductor film having a high filling rate and film density, high conductivity, and excellent migration resistance. [Brief description of the drawings]

[0031] [Figure 1] FIG. 2 is an external view of a laminated inductor. [Diagram 2] FIG. 2 is an exploded view of an element part of the laminated inductor. [Diagram 3] FIG. 2 is a simplified cross-sectional view taken along axis XX in FIG. 1. [Figure 4] FIG. 4 is a simplified enlarged view of a part of FIG. 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The silver paste of the present invention contains at least silver powder, a binder resin, and an organic solvent, The silver powder is selected from the following [1] to [4]: [1] The present invention includes a first silver powder (a) having a D50 of 3.50 to 7.50 μm and a second silver powder (b) having a D50 of 0.80 to 2.70 μm, where D50 is the 50% value in the volume-based cumulative fraction determined by laser diffraction particle size distribution measurement; [2] The copper content of the entire silver powder is 10 to 5000 ppm by mass; [3] The copper content of the second silver powder (b) is 80 ppm by mass or more; [4] the first silver powder (a) is substantially free of copper; The silver paste is characterized by satisfying all of the above conditions.

[0033] In the present invention, D10 and D50 respectively refer to the 10% and 50% values ​​in the volume-based cumulative fraction in laser diffraction particle size distribution measurement.

[0034] The silver paste of the present invention contains at least silver powder, a binder resin, and an organic solvent.

[0035] The silver powder according to the silver paste of the present invention, that is, the silver powder contained in the silver paste of the present invention, is not particularly limited in shape, particle size, production method, etc. as long as it can satisfy the requirements described below.

[0036] The silver powder according to the silver paste of the present invention includes a first silver powder (a) having a D50 of 3.50 to 7.50 μm and a second silver powder (b) having a D50 of 0.80 to 2.70 μm, where D50 is the 50% value in the cumulative fraction based on volume in laser diffraction particle size distribution measurement. That is, in the silver paste of the present invention, two types of silver powders having different D50s, that is, a mixed powder of the first silver powder (a) and the second silver powder (b), are used as the silver powder. In the silver paste of the present invention, the first silver powder (a) and the second silver powder (b) having different D50s are used in combination, thereby increasing the dry film density. In this specification, the symbol "~" indicating a numerical range indicates a range including the numerical values ​​written before and after the symbol "~" unless otherwise specified. That is, for example, the expression "3.50 to 7.50" is synonymous with "3.50 or more and 7.50 or less" unless otherwise specified.

[0037] The total copper content of the silver powder according to the silver paste of the present invention is 10 to 5000 mass ppm, preferably 30 to 500 mass ppm. When the copper content of the silver powder is within the above range, migration is unlikely to occur. On the other hand, if the copper content of the silver powder is less than the above range, migration is likely to occur, and if it exceeds the above range, the resistivity is large.

[0038] In the silver paste of the present invention, the second silver powder (b) contains 80 mass ppm or more of copper, while the first silver powder (a) does not substantially contain copper. The upper limit of the copper content of the second silver powder (b) is not particularly limited as long as the copper content of the entire silver powder satisfies the above range, but the copper content of the second silver powder (b) is preferably 10000 ppm or less, and particularly preferably 8000 ppm or less, in order to prevent the resistivity from becoming too large. In the present invention, the first silver powder (a) does not substantially contain copper means that the copper content in the first silver powder (a) is less than 50 mass ppm.

[0039] In the silver paste of the present invention, the copper content of the entire silver powder is 10 to 5000 mass ppm, preferably 30 to 500 mass ppm, and the first silver powder (a) does not substantially contain copper, so that the second silver powder (b) having a smaller D50 contains more copper among the first silver powder (a) and the second silver powder (b) which constitute the silver powder and have different D50s. In the silver paste of the present invention, the second silver powder (b) having a smaller D50 contains more copper, so that migration is less likely to occur and high conductivity can be exhibited.

[0040] The shape of the first silver powder (a) may be granular, flaky, or amorphous, but is preferably spherical. In the present invention, "spherical" refers to particles in which the average aspect ratio of any 50 particles within the field of view is within the range of 1.0 to 1.5 when observed with a SEM (scanning electron microscope). The average aspect ratio is preferably within the range of 1.0 to 1.3.

[0041] The D50 of the first silver powder (a) is 3.50 to 7.50 μm, preferably 3.70 to 7.50 μm, and particularly preferably 4.00 to 6.00 μm. When the D50 of the first silver powder (a) is within the above range, it is easy to control the D50 of the entire silver powder, and it is also easy to reduce the resistance value.

[0042] The shape of the second silver powder (b) may be granular, flaky or irregular, but is preferably spherical.

[0043] The D50 of the second silver powder (b) is 0.80 to 2.70 μm, may be 0.80 to 2.00 μm, and is preferably 0.80 to 1.80 μm. When the D50 of the second silver powder (b) is in the above range, a conductor film having high film density and good migration resistance can be easily obtained. In addition, the D10 of the second silver powder (b) is preferably 0.70 μm or more. When the D10 of the second silver powder (b) is in the above range, the occurrence of short circuits between conductor films can be easily suppressed.

[0044] The silver powder as a whole preferably has a D10 of 1.00 to 3.00 μm and a D50 of 3.00 to 7.00 μm. The silver powder as a whole preferably has a D10 of 1.20 to 2.00 μm and a D50 of 3.90 to 5.00 μm. When the silver powder as a whole has D10 and D50 satisfying the above requirements, the dry film density is increased and the content of small-diameter silver powder that is prone to migration is reduced, effectively suppressing short circuits between conductor films.

[0045] The content ratio of the first silver powder (a) in the silver powder ((first silver powder (a) / (first silver powder (a)+second silver powder (b)))×100) is preferably 40 to 95 mass%, particularly preferably 60 to 90 mass%. When the content ratio of the first silver powder (a) in the silver powder ((first silver powder (a) / (first silver powder (a)+second silver powder (b)))×100) is within the above range, the dry film density is increased and migration is less likely to occur.

[0046] Specific surface area S of the entire silver powder BET is preferably 0.10 to 0.30 m 2 / g, and particularly preferably 0.12 to 0.20 m 2 / g. The specific surface area of ​​the entire silver powder S BET By keeping S in the above range, the content of small-diameter silver powder, which is prone to migration, is low, so that short circuits between the conductor films are effectively suppressed. BET (m 2 / g) is the specific surface area determined by the BET method in which helium gas is adsorbed on the surface of silver powder.

[0047] The binder resin in the silver paste of the present invention is not particularly limited, and examples of the binder resin include those used in ordinary silver pastes. Examples of the binder resin include cellulose, acrylic resin, phenolic resin, epoxy resin, urethane resin, polyester resin, and polyethylene resin.

[0048] The organic solvent for the silver paste of the present invention is not particularly limited, and may be any organic solvent used in ordinary silver pastes. Examples of the organic solvent include alcohol-based, ether-based, ester-based, and hydrocarbon-based organic solvents, water, and mixed solvents thereof.

[0049] The higher the silver content in the silver paste, the more conductive the film can be obtained, but if the silver content is too high, the printability is reduced. AG is preferably 80.00 to 97.00 mass%, and particularly preferably 92.00 to 96.00 mass%. By having the silver powder content in the above range, both the electrical conductivity and the printability can be improved. The silver powder content C in the silver paste AG (% by mass) is the content ratio of silver powder to silver paste calculated by the formula "(silver powder content / silver paste mass) × 100".

[0050] The dry film density of the silver paste of the present invention is preferably 7.50 g / cm 3 The lower limit of the dry film density of the silver paste of the present invention is particularly preferably 7.60 g / cm. 3 and most preferably 7.80 g / cm 3 In addition, the upper limit of the dry film density of the silver paste of the present invention is preferably as high as possible as long as the printability is good. 3 ), and taking into consideration workability and productivity, a realistic limit is 8.50 g / cm 3The upper limit is about 15 mm. In addition, the method for controlling the dry film density can be controlled by a widely known general method, and examples of the method include adjusting the particle size distribution of the silver powder and its surface condition (smoothness, presence or absence of surface treatment, etc.), changing the binder resin or organic solvent used, or changing the type and amount of a dispersant added to the paste. In the present invention, the dry film density refers to the density of a dry film obtained by drying a coating film of the silver paste as it is without applying pressure. In the example described below, the silver paste to be measured is applied to a PET film with a thickness of about 150 μm, and then temporarily dried at 80 ° C. for 10 minutes, and then punched out with the PET film into a circular shape with a diameter of 15 mm. The PET film is further dried at 150 ° C. for 1 hour, and the PET film is peeled off. The mass W and volume V of the obtained dry film are measured to calculate W / V.

[0051] In the silver paste of the present invention, the binder content ratio C to the silver powder BDN is preferably 0.430 to 0.750% by mass, and particularly preferably 0.440 to 0.600% by mass. By having the binder content ratio relative to the silver powder within the above range, it is possible to increase the silver content in the silver paste while maintaining good printability. BND (% by mass) is the content ratio (% by mass) of the binder resin relative to the silver powder obtained by the formula "(content of binder resin in silver paste / content of silver powder in silver paste) x 100".

[0052] In the silver paste of the present invention, the specific surface area of ​​the entire silver powder is S BET (m 2 / g), and the content ratio of binder resin to silver powder is C BND (mass%), "C BND / S BET The value of " is preferably 2.00 to 3.40, and more preferably 2.50 to 3.10. BND / S BETWhen the value of is within the above range, the silver content in the silver paste can be increased while maintaining good printability, and as a result, a conductive film having a high dry film density, denseness, and high conductivity can be easily obtained.

[0053] The silver paste of the present invention satisfies all of the above requirements [1], [2], [3], and [4], thereby making it possible to obtain a dense, highly conductive film and form a conductor film with low resistivity, while also obtaining a conductor film with excellent printability and coating film shape, which also has excellent migration resistance and reduces the occurrence of short circuits between conductor films. In the experimental examples described below, after the silver paste of the present invention is screen-printed on a substrate to be printed, it is evaluated that the closer the contact angle (rectangularity) between the substrate and the coating film is to 90°, the more preferable the coating film shape (printing pattern) and the better the printability.

[0054] In the present invention, the method for producing silver powder is not particularly limited, but for example, the conventionally known atomization method, wet reduction method, CVD method, PVD method as described in Japanese Patent No. 3541939, spray pyrolysis method as described in Japanese Patent Publication No. 63-31522, and "method of pyrolyzing a pyrolytic metal-containing compound in a gas phase" as described in Japanese Patent No. 3812359 can be used to produce silver powder. Among them, the above-mentioned PVD method, spray pyrolysis method, or "method of pyrolyzing a pyrolytic metal-containing compound in a gas phase" is preferable in that it is easy to obtain silver powder that is spherical, highly crystalline, and has a uniform particle size.

[0055] The silver paste of the present invention can appropriately contain, as necessary, glass frit, inorganic compounds such as metal oxides, and additives that are typically used in silver pastes, such as plasticizers, viscosity adjusters, surfactants, dispersants, and oxidizers.

[0056] The silver paste of the present invention is produced in a conventional manner by kneading together silver powder, a binder resin, an organic solvent, and, where necessary, an inorganic oxide, an additive, and the like, and uniformly dispersing them to prepare a paste having a rheology suitable for screen printing and other printing methods.

[0057] The silver paste of the present invention is used for forming internal electrodes, external electrodes, and thick-film conductor circuits in electronic components such as multilayer ceramic capacitors, inductors, actuators, etc. In particular, the silver paste of the present invention is suitably used for forming internal electrodes of powder magnetic core materials, particularly multilayer inductors in which soft magnetic metal particles are used as the magnetic material.

[0058] In order to facilitate understanding of the "printability" in the present invention, a laminated inductor will be taken as an example for explanation below. Typically, a multilayer inductor 10 is composed of an element body 11, and a first external electrode 12 and a second external electrode 13 covering a pair of end faces of the element body 11, as shown in FIG.

[0059] As shown in FIG. 2, the element 11 is constructed by laminating magnetic layers A1 to A20 and internal electrode layers B1 to B17. The magnetic layers A1 to A20 are obtained by kneading core-shell type composite particles, in which the surfaces of soft magnetic iron alloy particles mainly composed of iron are covered with an insulating film made of resin or oxide film, together with an appropriate binder resin and organic solvent to prepare a magnetic paste, which is then formed into a sheet and dried. On the surfaces of the magnetic layers A3 to A19, the internal electrode layers B1 to B17 are formed in a predetermined pattern by a screen printing method. The silver paste of the present invention is used to form these internal electrode layers. One end of the internal electrode layer B1 is exposed on the end face of the magnetic layer A3 and is electrically connected to the external electrode 12, and one end of the internal electrode layer B17 is similarly electrically connected to the external electrode 13. The internal electrode layers B1 to B17 are electrically connected to each other via through-hole electrodes C1 to C16 formed in the thickness direction of the magnetic layers A3 to A19, and the internal electrode layers B1 to B17 are configured in a coil shape in the lamination direction as a whole. When the internal electrode layers B1 to B17 are formed on the magnetic layers A3 to A19, it is preferable that a magnetic layer (not shown) having a shape capable of filling the step caused by the film thickness of the internal electrode layers B1 to B17 is further laminated on the magnetic layers A3 to A19. Then, the element body 11 in which the magnetic layers A1 to A20 and the internal electrode layers B1 to B17 are laminated is subjected to a thermocompression bonding process and sintered at about 700°C, and then external electrodes 11 and 12 are formed on a pair of ends thereof to form a laminated inductor. Here, the external electrodes may be formed using the silver paste of the present invention, or may be formed using a conductive paste mainly composed of nickel or copper.

[0060] The cross section of the laminated inductor of FIG. 1 manufactured in this manner along the XX axis is shown in FIG. 3, and a part of it is enlarged and shown in FIG. 4. Note that both FIG. 3 and FIG. 4 are simplified diagrams and do not necessarily match the contents and structure shown in FIG. 2, including the number of layers. As shown in FIG. 3, the cross section of the internal electrode layer is ideally desired to be rectangular. However, in reality, when the silver paste is applied and printed on the substrate, the viscosity and fluidity of the paste affect the cross section, so that the actual cross section of the internal electrode layer is usually approximately trapezoidal as shown in FIG. 4. To make this shape closer to a rectangle, it is necessary to obtain a paste with high fluidity when printing the paste and high viscosity immediately after printing. However, there are a great number of parameters that must be controlled in the paste, and they affect each other in a complex manner, so it is no exaggeration to say that there are no cases in which the expected results or characteristics are obtained.

[0061] As described above, in this specification, "printability" means not only that the composition exhibits appropriate fluidity when printed by screen printing, gravure printing or the like, but also that the composition quickly exhibits high viscosity after printing, resulting in a coating film (conductor film) that is closer to a rectangular shape.

[0062] The silver paste of the present invention is suitably used as a fired silver paste used to form internal electrodes and external electrodes in ceramic electronic components such as multilayer ceramic capacitors, inductors, actuators, etc. For example, the silver paste of the present invention is used to form a conductor film by heat treatment at 700° C. or less.

[0063] The present invention will be described below based on specific experimental examples, but the present invention is not limited to these. EXAMPLES

[0064] <Manufacturing of silver powder> First, silver powders 1 to 21 listed in Table 1 were prepared based on the spray pyrolysis method described in JP-B-63-31522. That is, for silver powders 6, 8, 13 to 17, and 19 to 21, the copper content in the obtained silver powder was the value listed in the silver powder overall column in Table 1, and the D10 and D50 values ​​were adjusted by spray pyrolysis of an aqueous solution in which silver salt and copper salt were weighed and dissolved, and the collected silver powder was classified. For silver powders 1 to 5, 7, 9 to 12, and 18, the copper content in the obtained silver powder was the value listed in the first silver powder or second silver powder column in Table 1, and the D10 and D50 values ​​were adjusted by spray pyrolysis of an aqueous solution in which silver salt and copper salt were weighed and dissolved, and the collected silver powder was classified. Then, the obtained first silver powder and second silver powder were mixed to obtain a mixed powder as a silver powder. For each silver powder, the 10% value (D10) and 50% value (D50) in the cumulative volume fraction were determined using a laser diffraction particle size distribution analyzer. In addition, the specific surface area (S BET The aspect ratio of 50 randomly selected silver powder particles was measured by SEM (scanning electron microscope) image observation, and the average value was calculated. The results are shown in Table 1.

[0065] [Table 1]

[0066] In Table 1, when the silver powder consists of only one type of silver powder, the physical properties of the entire silver powder are the same as the physical properties of the one type of silver powder, and when the silver powder is a mixture of two types of silver powder, the physical properties of the entire silver powder are the physical properties of the mixture of the two types of silver powder.

[0067] (Examples 1 to 9 and Comparative Examples 1 to 13) The silver powder shown in Table 1 is mixed with the silver powder shown in Table 2 at the content C AG and ethyl cellulose was added at the content C shown in Table 2. BND The remainder was terpineol (TPO), and these were kneaded to prepare silver paste samples a to u. Next, each of the silver paste samples a to u was applied to a PET film in an area of ​​20 mm x 20 mm x 151 μm, dried at 80°C for 10 minutes, punched out using a 15 mm diameter punch, and further dried at 150°C for 1 hour. Next, the mass W and volume V of the resulting dried film were measured, and the dry film density was calculated using the formula W / V. The results are shown in Table 2. The acceptable standard for dry film density was 7.50 g / cm. 3 That's all. Next, the silver paste sample was applied and printed onto a ceramic substrate in the shape of a rectangular parallelepiped measuring 60 mm x 0.6 mm x 40 μm, and fired at 650°C in an oxidizing atmosphere (air) to form a conductive film, after which the electrical resistance was measured using the four-terminal method and the resistivity was calculated. The results are shown in Table 2. The pass standard for resistivity was set at 1.90 μΩ·cm or less.

[0068] [Table 2] 1) Content of silver powder in silver paste: (silver powder / silver paste) x 100 2) Ethyl cellulose content relative to silver powder: (Ethyl cellulose / silver powder) x 100

[0069] (Examples 10 to 18, Comparative Examples 14 to 26) A rectangular parallelepiped pattern was formed by screen printing using the silver paste samples a to u obtained above on a magnetic layer with a thickness of 30 μm that had been prepared in advance, and a magnetic layer was printed to fill in the steps due to the thickness of the pattern. Three sets of these were stacked, and magnetic layers for covers were stacked on the top and bottom. Next, the stack was thermocompressed, degreased in an oxidizing atmosphere, and then fired at 650°C to obtain a laminate. Next, the printability was evaluated using the obtained laminate. Specifically, the laminate was cut as shown in Figure 4, the rectangularity of the cross section of the conductive film was observed, and the average value of the angle corresponding to θ in Figure 4 was measured. The results are shown in Table 3. The acceptable standard for printability was 55° or more, and preferably 65° or more. Further, 25 laminates were prepared in the same manner as above, and the short-circuit rate of the laminates was measured. Specifically, electrical resistance was measured between the top and middle layers and between the middle and bottom layers of the three conductive films in the laminate, and this was repeated for the 25 laminates prepared. The ratio of the number of times that electrical continuity occurred to the total number of measurements was taken as the short-circuit rate. The results are shown in Table 3. The pass standard for the short-circuit rate was set to 5% or less, and preferably 3% or less.

[0070] [Table 3]

Claims

1. A method for manufacturing a laminated inductor having a laminate in which a plurality of magnetic layers and internal electrode layers formed on respective surfaces of the magnetic layers are laminated, and external electrode layers formed on end surfaces of the laminate and electrically connected to the internal electrode layers, comprising the steps of: The internal electrode layers are formed using a silver paste that contains at least silver powder, a binder resin, and an organic solvent and satisfies all of the following conditions [1] to [4]: A method for manufacturing a laminated inductor comprising the steps of: [1] A first silver powder (a) having a D50 of 3.50 to 7.50 μm, and a second silver powder (b) having a D50 of 0.80 to 2.70 μm, where D50 is the 50% value in the volume-based cumulative fraction measured by laser diffraction particle size distribution measurement; [2] The copper content of the entire silver powder is 10 to 5000 ppm by mass; [3] The copper content of the second silver powder (b) is 80 ppm by mass or more; [4] The first silver powder (a) is substantially free of copper.

2. 2. The method for manufacturing a laminated inductor according to claim 1, further comprising laminating a magnetic layer on said magnetic layer so as to fill in a step caused by the thickness of said internal electrode layer.

3. 3. The method for manufacturing a laminated inductor according to claim 1, wherein the internal electrode layers are electrically connected to each other via through-hole electrodes formed to penetrate the magnetic layers in a thickness direction.

4. 3. The method for producing a laminated inductor according to claim 1, wherein the laminate is formed by firing at 700[deg.] C. or less.

5. 3. The method for manufacturing a laminated inductor according to claim 1, wherein the D10 of the second silver powder (b) is 0.70 μm or more, when the 10% value of the volume-based cumulative fraction in laser diffraction particle size distribution measurement is defined as D10.

6. The method for manufacturing a laminated inductor according to claim 1 or 2, characterized in that the silver powder as a whole has a D10 of 1.00 to 3.00 μm and a D50 of 3.00 to 7.00 μm.

7. Further, the following [5]: [5] The total content C of the silver powder in the silver paste AG is 80.00 to 97.00% by mass; 3. The method for manufacturing a laminated inductor according to claim 1, wherein the above condition is satisfied.

8. The dry film density of the silver paste is 7.50 g / cm 3 3. The method for producing a laminated inductor according to claim 1, wherein the method is as described above.

9. The specific surface area of ​​the entire silver powder is S BET (m 2 / g), and the content ratio of the binder resin to the entire silver powder is C BND (mass%), C BND / S BET 3. The method for producing a laminated inductor according to claim 1, wherein the value of is 2.00 to 3.

40.

10. The specific surface area S of the entire silver powder BET 0.10 to 0.30 m 2 3. The method for manufacturing a laminated inductor according to claim 1, wherein the thickness of the laminated inductor is 1 / g.

Citation Information

Patent Citations

  • Photosensitive silver paste and image display unit using the same

    JP2003280179A

  • Conductive paste composition and laminated ceramic capacitor using it

    JP2004220807A

  • Metal paste, and film forming method using same

    JP2005174824A

  • Mixed conductive powder

    JP2005203304A

  • High crystalline flaky silver powder and its producing method

    JP2006111903A